Ablation of Bscl2/seipin in hepatocytes does not cause metabolic dysfunction in congenital generalised lipodystrophy - George D. Mcilroy; Sharon E. Mitchell; Weiping Han; Mirela Delibegović; Justin J. Rochford (The Company of Biologists, 2020)
Mutations affecting the BSCL2 gene cause the most severe form of congenital generalised lipodystrophy (CGL). Affected individuals develop severe metabolic complications including diabetes and hepatic steatosis. Bscl2-deficient mice almost entirely reproduce the CGL phenotype. Adipose tissue-specific loss of Bscl2 is also sufficient to cause early-onset generalised lipodystrophy in mice. However, these mice do not show severe metabolic dysfunction, even when challenged with a high-fat diet. Germline Bscl2 loss in mice and BSCL2 disruption in humans causes severe hepatic steatosis, and the encoded protein, seipin, has acknowledged roles in lipid accumulation. Given the critical role of the liver in glucose regulation, we speculated that intact hepatic Bscl2 expression may protect adipose tissue-specific Bscl2-deficient mice from metabolic disease. To investigate this, we generated a novel mouse model in which Bscl2 has been deleted in both adipose tissue and hepatocytes simultaneously using an adeno-associated viral vector. Despite achieving efficient disruption of Bscl2 in the liver, hepatic lipid accumulation and metabolic homeostasis was unaffected in mice fed a high-fat diet for 4 weeks. We also investigated the consequences of BSCL2 ablation in the human hepatocyte HepG2 cell line using CRISPR/Cas9 genome editing. No significant increases in lipid accumulation were observed in BSCL2 knockout cell lines. Overall, we reveal that Bscl2/BSCL2 does not appear to play a cell-autonomous role in the regulation of lipid accumulation in the liver. Loss of hepatic BSCL2 is therefore unlikely to contribute significantly to the development of hepatic steatosis or metabolic dysfunction in this form of CGL.